Associations of neopterin and kynurenine–tryptophan ratio with survival in primary sclerosing cholangitis. (3rd April 2021) - Dhillon, Amandeep Kaur; Rupp, Christian; Bergquist, Annika; Voitl, Robert; Folseraas, Trine; Trøseid, Marius; Midttun, Øivind; Ueland, Per M.; Karlsen, Tom H.; Vesterhus, Mette; Kummen, Martin; Hov, Johannes R.
Abstract: Background and aims: Biomarkers of inflammation may be of clinical utility in primary sclerosing cholangitis (PSC). We aimed to investigate the interferon gamma-related biomarkers neopterin and kynurenine–tryptophanratio (KT-ratio) in PSC. Methods: Circulating neopterin, tryptophan and kynurenine were measured with LC-MS/MS in multiple cross-sectional cohorts comprising in total of 524 PSC patients and 100 healthy controls from Norway, Germany and Sweden. Results: Neopterin and KT-ratio were significantly increased in PSC patients compared with controls in both a discovery and a validation cohort from Norway. Furthermore, high neopterin and KT-ratio levels were associated with a shorter transplantation-free survival in the PSC patients in the Norwegian discovery cohort and the German validation cohort. However, in the validation PSC cohort from Sweden, no relationship between neopterin and KT-ratio and liver transplantation-free survival was observed. The correlations between neopterin and KT-ratio were moderate to strong and similar in all cohorts (rho 0.50–0.67). Neopterin and KT-ratio also correlated with C-reactive protein (rho 0.17-0.63) and revised Mayo risk score (rho 0.23–0.42) in all cohorts. Conclusions: Neopterin and KT-ratio were elevated in PSC and associated with liver transplantation-free survival in two independent PSC cohorts, highlighting a possible role of interferon gamma-driven inflammation in the pathogenesis. However, the lack of association with survival in one of the cohorts reduces the potential clinical value of neopterin and KT-ratioas biomarkers and highlights the need to validate new biomarkers in PSC in multiple cohorts.